Vanishing solitary osteochondroma of humerus following trauma: A case report - Isam Sami Moghamis (16329146) (2023)
Osteochondromas are the most common benign tumors of the bone. Mainly these lesions affect the long-bone metaphysis and usually are asymptomatic. When complications develop from these lesions, then they become symptomatic and surgical resection may become indicated. Spontaneous resolution of osteochondroma is rare. There have been fewer case reports about this condition. We are reporting 16 years old, male, who sustained direct trauma to his shoulder and presented with fracture at the base of a solitary osteochondroma. Complete resolution of the lesion occurred without any surgical intervention 18 months following the fracture. Other Information Published in: Trauma Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1016/j.tcr.2023.100874